A Review of Feedback Models and Theories: Descriptions, Definitions, and Conclusions - Lipnevich, Anastasiya A.; Panadero, Ernesto (Frontiers in Education, 2021)
The positive effect of feedback on students’ performance and learning is no longer disputed. For this reason, scholars have been working on developing models and theories that explain how feedback works and which variables may contribute to student engagement with it. Our aim with this review was to describe the most prominent models and theories, identified using a systematic, three-criteria approach. We selected fourteen publications and described definitions, models, their background, and specific underlying mechanisms of feedback processes. We concluded the review with eight main points reached from our analysis of the models. Our hope is that our conclusions will inform the field and help both scholars and educators to select appropriate models to frame their research and intervention development.